ANALYSIS OF CONNECTING ROD USING REVERSE ENGINEERING METHOD AND MODIFY THE DESIGN USING POLYNOMIAL CURVE - MR. NILESH U. GUNJAL,; PROF. VILAS B. SHINDE, (International Journal of Innovations in Engineering Research and Technology, 2021)
Connecting rod is the most important part in the automobile sector it forms the link between piston and crankshaft. It is mostly used for the conversion of the reciprocation motion to rotary motion. Connecting rod receives the forces from the piston which are continuously varying in nature so stress on the connecting rod is continuouslyvarying. So the design of the connecting rod is the most important criteria. The design changes of the connecting rod is not economical, because today’sconnecting rod is having cross section of I and the I cross section is having the largest load carrying capacity per unit weight of the connecting rod so the cross section change is not possible so only the corner radius of the connecting rod would be the option for the change without much more stress concentration.